Biodiversity Analysis of Protected Forests in Central Kalimantan: Implications for Conservation and Sustainable Management - Dwi Syamsih (Journal of Horizon, 2024)
Protected forests in Central Kalimantan are vital reservoirs of biodiversity, housing diverse flora and fauna crucial for local and global ecosystems. Despite their ecological significance, these forests face imminent threats from deforestation, illegal encroachment, and climate change, jeopardizing their biodiversity and ecological integrity. This study aims to assess the biodiversity of Central Kalimantan's protected forests and explore its implications for conservation and sustainable management. The research methodology employs a comprehensive approach, integrating field surveys, laboratory analysis, and community engagement. Field surveys involve transect walks, camera traps, and direct observations to inventory flora and fauna. Soil and water analyses assess habitat conditions, while participatory approaches engage local communities in forest management. Findings reveal a rich diversity of flora and fauna, including rare and endemic species such as Shorea stenoptera and Dipterocarpus grandiflorus. High Shannon-Wiener and Simpson diversity indices indicate a healthy ecosystem, but deforestation and illegal encroachment pose significant threats, fragmenting habitats and disrupting species survival. Climate change exacerbates these challenges, necessitating adaptation strategies for ecosystem resilience. Community participation emerges as pivotal in conservation efforts, leveraging traditional knowledge and fostering sustainable livelihoods. Collaboration among stakeholders is essential for effective forest management, emphasizing the need for holistic conservation strategies. In conclusion, this study underscores the urgent need for conservation action to safeguard the biodiversity of Central Kalimantan's protected forests. By integrating scientific research with community engagement, policymakers and stakeholders can develop effective strategies to conserve these invaluable ecosystems, ensuring their sustainability for future generations.